COSTLY-DEFENSE SYSTEMS VERSUS PRODUCTIVE INVESTMENTS: THE CASE OF SINGAPORE’S 1st GENERATION MILITARY BUILD-UP (THE 1960s-1980s) - Wicaksono, Wirawan Hanindito; Arief, Ruslan (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2022)
Choosing a costly defense over an economically productive investment is always a nightmare for national policymakers. Despite the dilemma, Singapore came up as an anomaly with its decision in investing a remarkable amount of defense budget, reaching 4.5% of its GDP (Gross Domestic Product) and ranging around 15-30% of its annual government spending and still succeeding in developing its economy, while some do not. Therefore, drawing from what happened in the early period of Singapore’s independence, this study aims to figure out how the country justified its decision to choose a costly defense investment over a productive investment during this period and how the Singapore government decided to spend almost 40% of its annual budget on defense. Through historical analysis and literature studies, this study finds that the decision to choose a costly defense investment over an economically productive investment is justifiable under specific circumstances: first, when a nation deals with threats that would cost the nation future and survivability; second, the ability to implement the policy effectively and efficiently; third, is the ability to set how much is enough, the top limit of defense investment; and fourth, the existence of potential economic benefits.